(untitled) (Journal of Economic Research & Business Administration, 2022)
The article analyzes the indicators of innovation statistics and assesses of Kazakhstani innovation and research capacity. The purpose of the article is to assess and analyze the innovative potential of Kazakhstan based on the results of statistics from government departments and data from international rating agencies. There was a comparative analysis between the official data of the annual bulletins of the Bureau of National Statistics “On innovation activities of enterprises in the RoK”, “Key indicators of R&D activities in the RoK” and annual reports of the Global Competitiveness Index. Innovation capacity is the key factor affecting country competitiveness that requires presence of an ecosystem for stimulating and supporting innovation. For this, the following conditions are necessary: sufficient investment in R&D; the presence of high-quality scientific research institutions that can generate the basic knowledge needed to build the new technologies; extensive collaboration in research and technological developments between universities and industry; and the protection of intellectual property. The analysis results have revealed that the following factors, such as the lack of funding for R&D and innovation activities, a small share of innovation activities among companies and the low quality of research institutes, create barriers for complete development of the Kazakhstan innovation capacity. Comparison of the indicators of the international ranking of the GCI and domestic statistic data in innovation and R&D, including the assessment methodology and analysis of questions and associated answers of the Executive Opinion Survey, shows that domestic statistics should also track the following indicators, such as the development of clusters, the quality of research institutions, the sophistication of buyers and cited publications. In addition, it was noted that for a more objective assessment of the country’s competitiveness, as well as for the development of an innovation policy, it is advisable to use other alternative results of world rankings, in particular, the results of the Global Innovation Index and the world competitiveness ranking of the International Institute of Management Development (IMD World Competitiveness Yearbook – IMD WCY). Key words: innovation, science, innovation capacity, knowledge economy, innovation activity, competitiveness index.